Salmon trade duration: The application of firm-level trade transaction data from the Norwegian salmon industry - Tinoush Jamali Jaghdani; Ulf Johansen; Maitri Thakur; Thomas Glauben (Agribusiness, 2024)
Seafood products are mainly provided through trade to international markets and Norway is the major international player for the export of salmon products. It is argued that fresh or chilled salmon, which are perishable products and Norway's main seafood export, need stable trade partners to safely and properly reach consumption markets. In this study, the firm-to-firm level trade transactional data for both exporters and importers for the 2005–2018 period was utilized for a trade duration analysis. The Kaplan–Meier survival estimators, Cox proportional hazard model, and frailty model were used to study the stability of trade relations between the partners through survival and hazard models. The study considers the heterogeneous firm trade model along with a theoretical framework. The results show that, on average, the trade duration for the salmon trade between firms is 2.39 years, which is relatively low for a perishable product such as salmon. It shows that the market entry and exit is relatively fast, and that the survival rate between the EU as a major demand market and non-EU countries is not very different. However, core and periphery markets can be defined by considering the survival rate, as major processing hubs in the EU, such as Poland and France as core markets, have higher survival rates compared with other countries that can be considered peripheries. Both extensive and intensive margins were found to reduce the hazard ratio. Different hazard ratios were also found between different types of exporter or ones utilizing different means of transport. We conclude that the trade duration between the partners can be increased if the competition in the market increases, which is probably possible in markets like the United~States where other exporters such as Chile are available.
Keywords: 630; Cox proportional hazard model; frailty; Kaplan-Meier survival; Norway; salmon; trade duration; trade spells